Immunotoxins: Targeted Toxin Delivery for Cancer Therapy - Xin Mei; Junsheng Chen; Jing Wang; Jianwei Zhu (Georg Thieme Verlag KG, 2019)
Immunotoxins are proteins that consist of a protein toxin conjugated to a specific targeting moiety. The targeting moiety is usually an antibody or ligand, such as monoclonal antibody, antibody fragment, a cytokine, or a growth factor. The toxins usually come from plant toxins, bacterial toxins, or human-origin cytotoxic elements. Nearly all toxins work by enzymatically inhibiting protein synthesis. After binding to antigens or receptors on target cell surfaces, immunotoxins are internalized and translocated to the cytosol where they can kill the cells. Immunotoxins have demonstrated high cytotoxicity to cancer cells and to date two immunotoxins have been approved by U.S. Food and Drug Administration on the markets for the treatment of hematological tumors: Lumoxiti and Ontak. Many other molecules are under development or clinical trials for different forms of cancer. Although immunotoxins exhibit great potency in xenograft model systems and early clinical trials, there are obstacles that limit successful treatments, including immunogenicity, nonspecific toxicity, and poor penetration. However, efforts are underway to address these problems. In this review, we summarize immunotoxins currently in clinical trials for either hematological tumors or solid tumors, outline the design of immunotoxins utilizing variety of components, and discuss the prominent examples of redesigned immunotoxins with reduced immunogenicity and nonspecific toxicity, as well as the strategies in manufacturing immunotoxins. With further improvements, it is anticipated that immunotoxins will play an increasing role in cancer therapy.